2008
DOI: 10.1021/tx800174a
|View full text |Cite
|
Sign up to set email alerts
|

Replication Bypass of the Acrolein-Mediated Deoxyguanine DNA-Peptide Cross-Links by DNA Polymerases of the DinB Family

Abstract: DNA–protein cross-links (adducts) are formed in cellular DNA under a variety of conditions, particularly following exposure to an α,β-unsaturated aldehyde, acrolein. DNA–protein cross-links are subject to repair or damage-tolerance processes. These adducts serve as substrates for proteolytic degradation, yielding DNA–peptide lesions that have been shown to be actively repaired by the nucleotide excision repair complex. Alternatively, DNA–peptide cross-links can be subjected to replication bypass. We present ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 62 publications
2
88
2
Order By: Relevance
“…Previous investigations have revealed that the ability of DNA polymerases to bypass DNA-peptide conjugates is dependent on the lesion size, the attachment site within the DNA, and polymerase identity (10,(21)(22)(23)(24)(25)(26)(27)(28)(29). Lloyd and co-workers (26) have reported that human polymerase (hpol) and its Escherichia coli orthologue pol IV were able to catalyze error-free primer extension past DNA templates containing tetra-and dodecapeptides conjugated to the N 2 position of guanine via a trimethylene linker.…”
Section: Dna-protein Cross-links (Dpcs)mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations have revealed that the ability of DNA polymerases to bypass DNA-peptide conjugates is dependent on the lesion size, the attachment site within the DNA, and polymerase identity (10,(21)(22)(23)(24)(25)(26)(27)(28)(29). Lloyd and co-workers (26) have reported that human polymerase (hpol) and its Escherichia coli orthologue pol IV were able to catalyze error-free primer extension past DNA templates containing tetra-and dodecapeptides conjugated to the N 2 position of guanine via a trimethylene linker.…”
Section: Dna-protein Cross-links (Dpcs)mentioning
confidence: 99%
“…Lloyd and co-workers (26) have reported that human polymerase (hpol) and its Escherichia coli orthologue pol IV were able to catalyze error-free primer extension past DNA templates containing tetra-and dodecapeptides conjugated to the N 2 position of guanine via a trimethylene linker. hpol was capable of bypassing both 4-and 12-mer peptides conjugated to N 6 of adenine via a trimethylene linkage, with correct base (dT) inserted opposite the adduct (27).…”
Section: Dna-protein Cross-links (Dpcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…ΔdinB strains are sensitive to DNA-damaging agents, nitrofurazone (NFZ) and 4-nitroquinolone-1-oxide (4-NQO), and DinB preferentially and accurately bypasses a structural analog of the major NFZ-induced N 2 -dG lesion as well as certain other N 2 -dG adducts (10)(11)(12)(13). NusA is an essential, multidomain protein that functions in both termination and antitermination of transcription, and is associated with the RNA polymerase (RNAP) throughout the elongation and termination phases of transcription (14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…For example, treatment with a cytidine analog, azacytidine C, results in covalently linked methyltransferase-DNA adducts that cause blockage of DNA replication in vivo (49). This blockage may be overcome by the action of specialized, translesion synthesis DNA polymerases that have been shown to be required for bypassing DNA-peptide cross-links, the potential intermediates generated during processing of DPCs (50). A similar role can be predicted for the helicases, rationalizing for the existence of several specialized helicases that participate in processing of blocked replication forks via different repair processes in a lesion-specific manner.…”
Section: Discussionmentioning
confidence: 99%